The Influence of Work-Life Balance and Burnout on Employee Performance through Work Motivation as an Intervening Variable at the Inspectorate Office of Mahakam Ulu Regency - Sudarwati, Anastasia Natalia; Yudhyani, Eka; Irwan, Sayid (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Employee performance was one of the key factors determining the success of an organization in achieving its goals. In this context, Work Life Balance (WLB), Burnout, and Motivation were considered important variables believed to influence performance. Many employees faced challenges in balancing job demands and personal life, which, if not managed properly, could trigger Burnout and decrease work motivation. Therefore, this study was conducted to examine the direct and indirect effects of Work Life Balance and Burnout on Employee Performance through Motivation as a mediating variable. This research used a quantitative approach with a survey method. The sample consisted of 31 respondents selected based on predetermined criteria. Data were collected using a questionnaire, and analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS version 4 software. The tests conducted included convergent validity, discriminant validity, and instrument reliability. This study found that Work-Life Balance has a positive and significant effect on work motivation, while Burnout has a negative and significant effect. The better the employees' balance between work and personal life, the higher their work motivation, in line with Maslow's hierarchy of needs. Conversely, increased physical and emotional exhaustion leads to a decline in motivation. However, both Work-Life Balance and Burnout do not directly influence employee performance significantly. This implies that employees may continue to perform professionally regardless of their personal balance or level of fatigue. On the other hand, motivation has a proven positive and significant impact on performance. In other words, Work-Life Balance indirectly enhances performance through motivation, while Burnout indirectly diminishes it. Therefore, motivation serves as a crucial mediator linking Work-Life Balance and Burnout to employee performance within the organization.